PERENCANAAN LINGKUNGAN PERMUKIMAN NELAYAN KAMPUNG LERE KOTA PALU - Basri, Iwan Setiawan (MEKTEK, 2009)
The growth fisherman settlement is a natural event and this phenomenon is also happened at Kampung Lere so that it taudification as well as inconvenient arrangement. This will potentially decrease environmental quality. The purpose of this research is to assess the possibility of developing a fisherman settlement in kampong Lere without ignoring the environment quality by settlement environmental planning. The research is conducted on August 2002 by survey. The acquired data were then compiled and analyzed by qualitative analysis. The sample included all houses and building in the area. The study area is 31,64 Ha. The result shows that the residence fisherman at Kampong Lere, is to be kept. Settlement environmental planning concept; (1) the sustainability of fresh water, (2) Managing well drainage system, (3) the availability of waste management systems, (4) Conducting Road and pedestrian access system (6) Protection from abrasion by building dam and green program, (7) Proportionally managing border of river and beach, i.e. 30 - 100 m of apex tide sea-water counted from river, and k, and (8 ) Improving physical quality